Green Human Resource Management Syariah as a Transformation of the Concept of Sustainable Human Resource Management - Kristiyanti, Mariana; Kuncoro, Amin (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2025)
The purpose of this research is to explain the concept of implementing Green Human Resources Management Sharia (GHRMS) as a company strategy in the form of efforts to increase productivity and the company's commitment to maintaining sustainability, then quantified to strengthen the research findings so that they are more comprehensive. This research produces the latest concept; the success of an organization in implementing green human resources management sharia which is reflected in the performance of Islamic-based employees able to encourage more concern for the environment and apply it in everyday life; training and development facilitated by the organization so that employees can understand better with the training accompanied by development carried out by the organization; compensation and benefits for employees by providing awards and compensation as a form of concern for greening the environment, and organizational culture is able to support green human resources management sharia activities so that a resilient organizational life is created because it is supported by intense spirituality. In the future, research can be developed to increase productivity and company commitment to maintaining environmental sustainability based on Islamic values.